Modulation of protein-interaction states through the cell cycle - Dai, Lingyun (2019)
Global profiling of protein expression through the cell cycle has revealed subsets of periodically expressed proteins. However, expression levels alone only give a partial view of the biochemical processes determining cellular events. Using a proteome-wide implementation of the cellular thermal shift assay (CETSA) to study specific cell-cycle phases, we uncover changes of interaction states for more than 750 proteins during the cell cycle. Notably, many protein complexes are modulated in specific cell-cycle phases, reflecting their roles in processes such as DNA replication, chromatin remodeling, transcription, translation, and disintegration of the nuclear envelope. Surprisingly, only small differences in the interaction states were seen between the G1 and the G2 phase, suggesting similar hardwiring of biochemical processes in these two phases. The present work reveals novel molecular details of the cell cycle and establishes proteome-wide CETSA as a new strategy to study modulation of protein-interaction states in intact cells.